2008
DOI: 10.1016/j.ophtha.2007.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Intraocular Pressure before and during 9 Years of Treatment in the Collaborative Initial Glaucoma Treatment Study

Abstract: Methods-After randomization to initial surgery or medications, patients were followed at sixmonth intervals. IOP was measured by Goldmann applanation tonometry. Predictive factors for IOP at baseline and during follow-up were analyzed using linear mixed models. Main Outcome Measure-IOP at baseline and during follow-up.Results-The mean baseline IOP was 27.5 mmHg (standard deviation, 5.6 mmHg). Predictive factors for higher baseline IOP included younger age (0.7 mmHg per 10 years), male sex (2.4 mmHg higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 25 publications
0
44
2
2
Order By: Relevance
“…On the other hand, Law et al [6] report that a younger age is a risk factor for surgical failure of repeat trabeculectomy with MMC because older patients may have fewer activated fibroblasts and inflammatory cells than younger patients. Younger age was also found to be associated with higher IOP during 9 years of follow up in the Collaborative Initial Glaucoma Treatment Study [12]. In our study, however, age was not a significant risk factor in univariate analysis.…”
Section: Discussioncontrasting
confidence: 56%
“…On the other hand, Law et al [6] report that a younger age is a risk factor for surgical failure of repeat trabeculectomy with MMC because older patients may have fewer activated fibroblasts and inflammatory cells than younger patients. Younger age was also found to be associated with higher IOP during 9 years of follow up in the Collaborative Initial Glaucoma Treatment Study [12]. In our study, however, age was not a significant risk factor in univariate analysis.…”
Section: Discussioncontrasting
confidence: 56%
“…A new disposable probe was used for each patient. The measurement of the IOP with the GAT was performed by the following protocol [10,11]: a drop of 0.25% fluorescein with 0.5% proparacaine was administered topically in each eye, and the average of 2 sequential measurements were recorded; if the 2 measurements differed by >2 mm Hg, a 3rd measurement was made, and the median of the 3 measurements was recorded. Three consecutive measurements were made by the NCT, and the average was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The fact, however, that glaucoma treatment is considered palliative rather than curative as well as the general absence of symptoms in glaucoma patients increases their risk of non-compliance. Analysis of the Collaborative Initial Glaucoma Treatment Study identified an important role of compliance for IOP control during treatment [5]. In the light of these findings, high rates of non-compliance with glaucoma treatment in different populations constitute a significant public health concern.…”
Section: Introductionmentioning
confidence: 99%